2017
DOI: 10.1016/j.phpro.2017.09.060
|View full text |Cite
|
Sign up to set email alerts
|

Results from a Prototype Proton-CT Head Scanner

Abstract: We are exploring low-dose proton radiography and computed tomography (pCT) as techniques to improve the accuracy of proton treatment planning and to provide artifact-free images for verification and adaptive therapy at the time of treatment. Here we report on comprehensive beam test results with our prototype pCT head scanner. The detector system and data acquisition attain a sustained rate of more than a million protons individually measured per second, allowing a full CT scan to be completed in six minutes o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 11 publications
3
23
0
Order By: Relevance
“…Prototype pCT scanners have been designed and constructed (Takada et al 25 1988, Coutrakon et al 2013, Pettersen et al 2016, Esposito et al 2018. In recent studies, the RSP accuracy achieved by some of these prototypes has been reported to be better than 1.6% for three inserts (Esposito et al 2018) and 1.39% for seven inserts (Giacometti et al 2017). For the same seven inserts, Volz et al (2018) achieved accuracy better than 1% using helium ions with a 30 pCT prototype.…”
Section: Introductionmentioning
confidence: 99%
“…Prototype pCT scanners have been designed and constructed (Takada et al 25 1988, Coutrakon et al 2013, Pettersen et al 2016, Esposito et al 2018. In recent studies, the RSP accuracy achieved by some of these prototypes has been reported to be better than 1.6% for three inserts (Esposito et al 2018) and 1.39% for seven inserts (Giacometti et al 2017). For the same seven inserts, Volz et al (2018) achieved accuracy better than 1% using helium ions with a 30 pCT prototype.…”
Section: Introductionmentioning
confidence: 99%
“…The goal of this work was to investigate the effect of such events on the accuracy of pCT with the prototype detector developed by the US pCT collaboration (Bashkirov et al 2016a, Johnson et al 2017 in Monte Carlo simulations. We investigate the performance of the usual 3 σ WEPL filter and assess the potential of using the ∆E-E filtering technique recently proposed to identify nuclear fragmentation events in helium ion CT (HeCT) with the scanner energy/range detector (Volz et al 2018) to identify nuclear interaction events in pCT.…”
Section: Introductionmentioning
confidence: 99%
“…A calibration procedure that transforms the detector single‐proton measurement to WEPL is necessary and is discussed in Bashkirov et al The pCT collaboration has developed an improved version in which a polystyrene wedge phantom is used in Ref. [] instead of the stepped pyramid phantom. In addition to the wedge, four polystyrene blocks are required to bring the proton Bragg peak into each stage of the five‐stage plastic scintillator detector …”
Section: Methodsmentioning
confidence: 99%